IMPLEMENTATION OF THE ACCELERATED STUNTING REDUCTION MOVEMENT PROGRAM IN THE DISTRICT KUBU RAYA - SUKARMAN SUKARMAN (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2023)
This research aims to find out in depth about the implementation of the stunt Reduction acceleration Program in stronghold Raya Regency it is expected that the team for the stunt Reduction acceleration at the district levels will b able to synergize ( Kepong basket ) in an effort to prevent and deal with stunting cases. in this study, there are two points of discussions, namely: 1) communications, information and health services for prospective brides and grooms, and 2) identification and Learning more about stunt carried out by the Community Health Center of River Raya In. the persistent efforts limit been made by the Government of stronghold Raya Regency so that it claimed a significant reduction in the prevalence of stunting in 2020 which was around 13.4%, while in 2021 it decreased again to around 7.9% and there was another decrease in 2022 which was around 6.8 % . however, the Government of stronghold Raya hopes that in 2024, Kubu Raya can b in the position of 0% (Zero stunt). By taking into accounts the formulations of the existing problems, this research aims to describe and analyze the Implementation of the stunt Reduction acceleration Program in this area, especially with regard to the supports and inhibiting factors in the Program Implementation. the levels of community participation which is still low, there is a different perception about stunting and coordination between institutions or agencies that is not optimal certainly pose a challenge in implementing the stunt Reduction acceleration Program in Kubu Raya regencyKeywords:Keywords: Policy Implemenation, The Accelarated Stunting Reduction, Movement Program